Avaliação da atividade anticâncer in vitro de extratos de Aristolochia spp. e de seus produtos de bioconversão por Battus polydamas - Soares, Aparecida Rios (2021)
Cancer is the name given to the disorderly growth of cells forming a cell mass, called a tumor. In this sense, researches carried out with plants of the Aristolochia genus demonstrated its medicinal purposes for anticancer activity. Furthermore, other studies have reported that after the ingestion of these plants by caterpillars, a process called bioconversion occurs, thus obtaining possible new prototype candidates for new drugs. The objective of this work was to evaluate an in vitro anticancer activity of Aristolochia spp. and its bioconversion products performed by Battus polydamas butterflies, in neoplastic cell lines (B16-F10 and 786-0) and in non-neoplastic cell lines (NIH / 3T3), as well as calculating the selectivity index of the extracts. To perform the in vitro assays, it was used for cytotoxicity test with Sulforrhodamine B (SRB) dye. The methanol extracts with the best results were: Methanolic extract from the leaves of Aristolochia galeata (GI50 = 32,96 µg / mL in the line B16-F10) and methanolic extract from the feces of B. polydamas caterpillars fed on Aristolochia gigantea leaves (GI50 = 35,68 µg/mL in the 786-0) lineage. Methanolic extracts from A. gigantea leaves showed GI50 55,58 µg/mL and Selectivity Index (SI) = 4,74; while the feces of B. polydamas caterpillars fed on A. gigantea leaves presented GI50 35,68 µg/mL and IS= 6,93; indicating that they are more active in a neoplastic lineage when compared to the normal one. Given the results found in this research, this work suggests that a process of bioconversion by B. polydamas caterpillars may have occurred after the ingestion of the plant A. gigantea and its metabolism by this insect, when tested in the 786-0 lineage. Therefore, further studies are needed to elucidate the bioconversion process by insects and the mechanism of action of these extracts.